Oral hygiene protocol in patients diagnosed with ventilator-associated pneumonia and admitted to ICU: An integrative review (Research, Society and Development, 2023)
This integrative review aims to evaluate hygiene protocols in patients diagnosed with ventilator-associated pneumonia and admitted to the ICU. The articles were published in the last 5 years and the bibliographic survey was carried out through online access to VHL Brasil, MEDLINE, LILACS and Pubmed in English, Portuguese and Spanish between the years 2017 and 2022. Eligibility criteria included: adult patients older than 18 years; cross-sectional studies; cohorts; clinical and experimental trials and articles that addressed hygiene and protocols, with sixteen studies ultimately being used in the research. Through the results, it is possible to note that the presence of a hygiene protocol for patients in the intensive care unit is effective in preventing and developing VAP. The present work suggests a positive association between these protocols and the prevention of ventilator-associated pneumonia, however, more detailed studies are needed to create a standard and efficient protocol.